Apexogenesis and revascularization treatment procedures for two traumatized immature permanent maxillary incisors: a case report - Maryam Forghani; Iman Parisay; Amir Maghsoudlou (Korean Academy of Conservative Dentistry, 2013)
Traumatic injuries to an immature permanent tooth may result in cessation of dentin deposition and root maturation. Endodontic treatment is often complicated in premature tooth with an uncertain prognosis. This article describes successful treatment of two traumatized maxillary central incisors with complicated crown fracture three months after trauma. The radiographic examination showed immature roots in maxillary central incisors of a 9-year-old boy with a radiolucent lesion adjacent to the right central incisor. Apexogenesis was performed for the left central incisor and revascularization treatment was considered for the right one. In 18-month clinical and radiographic follow-up both teeth were asymptomatic, roots continued to develop, and periapical radiolucency of the right central incisor healed. Considering the root development of these contralateral teeth it can be concluded that revascularization is an appropriate treatment method in immature necrotic teeth.